Activist stabilization policy and inflation: The Taylor rule in the 1970s - Athanasios Orphanides (Goethe University Frankfurt, Center for Financial Studies (CFS), 2002)
A number of recent studies have suggested that activist stabilization policy rules responding to inflation and the output gap can attain simultaneously a low and stable rate of inflation as well as a high degree of economic stability. The foremost example of such a strategy is the policy rule proposed by Taylor (1993). In this paper, I demonstrate that the policy settings that would have been suggested by this rule during the 1970s, based on real-time data published by the U.S. Commerce Department, do not greatly differ from actual policy during this period. To the extent macroeconomic outcomes during this period are considered unfavorable, this raises questions regarding the usefulness of this strategy for monetary policy. To the extent the Taylor rule is believed to provide a reasonable guide to monetary policy, this finding raises questions regarding earlier critiques of monetary policy during the 1970s.
urn:nbn:de:hebis:30-10050
Keywords: E3; E52; E58; 330; Great Inflation; Taylor Rule; Output Gap; Real-time Data